2019
DOI: 10.1007/s12264-019-00406-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Muscular Nociceptive Afferents via the Activation of Cutaneous Nociceptors in a Rat Model of Inflammatory Muscle Pain

Abstract: Topical irritants such as capsaicin (CAP), peppermint oil (PO), and mustard oil (MO) are effective in relieving inflammatory muscle pain. We investigated the effects of topical irritants in a rat model of inflammatory muscle pain produced by injecting complete Freund's adjuvant (CFA) into the tibialis anterior muscle. CFAinduced mechanical hypersensitivity and the spontaneous activity of muscular nociceptive afferents, and decreased weight-bearing of the hindlimb were relieved by topical application of CAP, PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Our previous study revealed that noxious MS (> 43 • C) was able to drive long-distance neural reflex by activating peptidergic C-fibers (Su et al, 2015), which was in line with the results that noxious MS (about 50 • C) activated local SP-IR or CGRP-IR cutaneous terminals in the present study. In addition, cutaneous nerve transection abolished the analgesic effect of C-afferents in the skin over the inflamed muscle (Xie et al, 1995;Fang et al, 2020). In this study, cutaneous nociceptor-mediated noxious MS analgesia was also demonstrated, while it disappeared after skin nerve transection.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Our previous study revealed that noxious MS (> 43 • C) was able to drive long-distance neural reflex by activating peptidergic C-fibers (Su et al, 2015), which was in line with the results that noxious MS (about 50 • C) activated local SP-IR or CGRP-IR cutaneous terminals in the present study. In addition, cutaneous nerve transection abolished the analgesic effect of C-afferents in the skin over the inflamed muscle (Xie et al, 1995;Fang et al, 2020). In this study, cutaneous nociceptor-mediated noxious MS analgesia was also demonstrated, while it disappeared after skin nerve transection.…”
Section: Discussionsupporting
confidence: 61%
“…Nociceptive transmission could likewise trigger the descending inhibition system to regulate SRD neurons (Pinto et al, 2008). Besides, noxious stimuli on the contralateral side (Fang et al, 2020) or BL57 acupoint area (data not shown) over the inflamed muscle failed to relieve pain behavior, in turn implicating that presynaptic inhibition FIGURE 6 | Diagram of distinct primary afferent pathways of deep electroacupuncture (dEA)-and moxibustion-like stimulation (MS)-induced analgesic effects. dEA activates muscular A-fibers at the BL57 acupoint, while noxious MS or capsaicin (CAP) excites cutaneous C-fibers to improve muscle pain behavior via inhibiting spontaneous activity of muscular C-fibers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The receptive fields (RFs) of the neurons were identified with a mechanical press stimulator (ALMEMO2450, Ahlborn, Germany). Muscular nociceptive neurons in CFA rats were evoked by 200-mN pressure stimulation when there was no response to 60-mN pressure stimulation, as described previously ( Fang et al, 2020 ). Therefore, innocuous stimulation (60 mN) and noxious stimulation (200 mN) were chosen to identify WDR neurons and LTM neurons in the spinal dorsal horn, respectively.…”
Section: Methodsmentioning
confidence: 99%